Are chitosan natural polymers suitable as adjuvant/delivery system for anti-tuberculosis vaccines?. (August 2018) - Khademi, Farzad; Taheri, Ramazan-Ali; Yousefi Avarvand, Arshid; Vaez, Hamid; Momtazi-Borojeni, Amir Abbas; Soleimanpour, Saman
Abstract: Today, the effectiveness of the only approved tuberculosis (TB) vaccine, bacillus Calmette-Guerin (BCG), has encountered several serious problem in the control of TB infections including variable protection in adolescents and adults, the emergence of drug-resistant strains of Mycobacterium tuberculosis ( Mtb ) as well as HIV/AIDS co-infection. Various studies have shown that chitosan, a natural polymer, can serve as a potent carrier for the delivery of various hydrophilic molecules such as peptide, protein and drug agents due to some of its excellent characteristics including low toxicity, biodegradable and biocompatible properties and stability. Currently, these polysaccharide polymers have gained more attention as candidates for the adjuvant/delivery of anti-TB vaccines due to better cellular uptake, muco-adhesive characteristics, prolonged control release, persistent stimulation of the immune system, more efficient uptake by antigen processing cells (APCs), adjuvant/immunopotentiator function, and preventing antigen degradation in-vivo . The present study showed that the new generation of TB vaccine candidates when used in combination with chitosan and its derivatives as adjuvant or delivery system, could potently induce both protective and cell-mediated (CD4 and CD8) immune responses in animal models. In addition, they could also enhance protection against Mtb infection in TB-challenged mice and act as booster-vaccines to improve BCG-primed immunity and excellent prime-vaccines. The results of this study showed that parenteral and non-parenteral immunization of chitosan-based TB vaccines can induce appropriate immune responses; however, we suggest that based on some advantages of chitosan polymers and mucosal delivery route, non-parenteral immunization may be a better administration route for chitosan-based TB vaccines.